2012
DOI: 10.1002/cjoc.201200523
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic, Conjugate Reduction‐Aldol Addition Reaction of β′‐Oxoalkyl α,β‐Unsaturated Carboxylates

Abstract: Intramolecular conjugate reduction-aldol addition reactions of β'-oxoalkyl α,β-unsaturated carboxylates were performed in the presence of copper catalysts generated in situ from copper salts, phosphine ligands and silanes. Moderate to good yields and high diastereoselectivities were obtained in 15 min to 3 h using bis[(2-diphenylphosphino)phenyl] ether as the ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…20 We found that the copper complex of bis[(2-diphenylphosphino)phenyl] ether (DPEphos) is efficient in catalyzing the reduction of electron-deficient polar C=C double bonds conjugated to electron-withdrawing groups, 21 and that this complex can also catalyze reductive intramolecular aldol reactions in high yields and high diastereoselectivities. 22 Recently, we reported that high diastereoselectivities can be achieved in reductive intermolecular aldol reactions of unsaturated esters with ketones in the presence of a copper-4,5-bis(diphenylphosphino)-9,9-dimethylxanthene complex (Cu-Xantphos) catalyst. 23 In continuing our interest in copper hydride chemistry, we explored some novel copper(I) hydride-catalyzed multistep domino reactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…20 We found that the copper complex of bis[(2-diphenylphosphino)phenyl] ether (DPEphos) is efficient in catalyzing the reduction of electron-deficient polar C=C double bonds conjugated to electron-withdrawing groups, 21 and that this complex can also catalyze reductive intramolecular aldol reactions in high yields and high diastereoselectivities. 22 Recently, we reported that high diastereoselectivities can be achieved in reductive intermolecular aldol reactions of unsaturated esters with ketones in the presence of a copper-4,5-bis(diphenylphosphino)-9,9-dimethylxanthene complex (Cu-Xantphos) catalyst. 23 In continuing our interest in copper hydride chemistry, we explored some novel copper(I) hydride-catalyzed multistep domino reactions.…”
mentioning
confidence: 99%
“…We reasoned that the low conversion of maleate might be due to its low reactivity and to slow regeneration of copper hydride from enolate A (Scheme 1). The ease with which copper hydride is formed from a silane and a copper alkoxide, 26 coupled with the successful reductive intermolecular aldol addition reaction of unsaturated esters to carbonyls, 22 led us to introduce a carbonyl compound into the reaction system. If we assume that this carbonyl compound reacts with the copper enolate A, it should give the copper alkoxide C through an aldol reaction.…”
mentioning
confidence: 99%
“…[20] Very recently, we reported that copper hydride ligated with bis[(1,2-diphenylphosphino)phenyl] ether (DPEphos, Figure 1) could catalyze the reductive-intramolecular aldol addition of β'-oxoalkyl α,β-unsaturated carboxylates efficiently. [21] It is of great importance to perform more challenging reductiveintermolecular aldol addition domino reaction. Herein, we report that the intermolecular domino reaction of α,β-unsaturated carboxylates with ketones and a silane can be accomplished in the presence of CuH-DPEphos or CuH ligated with 4,5-bis(diphenylphosphino)-9,9dimethylxanthene (Xantphos), and that high diastereoselectivity can be achieved.…”
Section: Introductionmentioning
confidence: 99%